AYURVEDIC PERSPECTIVE ON PCOD AND INFERTILITY- A CASE STUDY - Nikitha Sirigere; Laxmi Kirana P (AYUSHDHARA, 2021)
Polycystic ovarian syndrome is a syndrome manifested by amenorrhea, hirsuitism and obesity associated with enlarged polycystic ovaries. It is the most common endocrine disorder in a woman of reproductive age. Furthermore it presents with infertility, abnormal bleeding, increased incidences of pregnancy loss and pregnancy related complications. Most patients present with elevated levels of androgens, Luteinizing hormone (LH), Oestrogen and Prolactin. The aetiology is multifactorial with the combination of genetic and environmental factors. Certain hypothesis related to etio-pathogenesis still remains unknown. Pelvic ultrasound is a major diagnostic tool determines the presence of multiple ovarian cysts ranging between 2mm and 9mm. Hormonal therapy and LOD (Laparoscopic Ovarian Drilling) are the only line of treatment in modern science whereas, Ayurvedic management offers lifestyle changes and medications having Tridoshahara, Srotoshodhaka & Anulomaka properties with its holistic approach. So, in the present study – Agnitundi vati, Sukumara kashayam and Nasya with Kalyanaka Ghrita, were administered in a patient complaining of irregular cycles due to PCOD and infertility. As a result of the treatment, patient not only regularised her cycles but even conceived. Nasya is the most effective method of restoring normal ovulation/ menstruation and thus maintains equilibrium of endocrine functions. The above said line of treatment was found to be cost effective and easily accessible. Further clinical trials can be conducted to assess the efficacy of the drugs.